2017
DOI: 10.1038/srep45913
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics by SWATH-MS reveals sophisticated metabolic reprogramming in hepatocellular carcinoma tissues

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide, and understanding its molecular pathogenesis is pivotal to managing this disease. Sequential window acquisition of all theoretical mass spectra (SWATH-MS) is an optimal proteomic strategy to seek crucial proteins involved in HCC development and progression. In this study, a quantitative proteomic study of tumour and adjacent non-tumour liver tissues was performed using a SWATH-MS strategy. In total, 4,216 proteins were reliably quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 58 publications
4
57
0
Order By: Relevance
“…For each enzymatic reaction, we took the fold change in gene expression values for the corresponding gene(s) in HCC with respect to NL, to be proportional to the variation in the corresponding E t (total enzyme) levels (Eqn 2, Materials and methods). Proteomic data of HCC samples are also available for a few of the enzymes in our model [37]. We compared the fold change in protein abundance in HCC with respect to NL (no etiology information is present in the data) with those of the gene expression variations, and find them to be in good agreement, lending additional support to the hypothesis that the gene expression variations used in the model are biologically meaningful (Table S3).…”
Section: Generating Hcc-specific Modelsmentioning
confidence: 62%
“…For each enzymatic reaction, we took the fold change in gene expression values for the corresponding gene(s) in HCC with respect to NL, to be proportional to the variation in the corresponding E t (total enzyme) levels (Eqn 2, Materials and methods). Proteomic data of HCC samples are also available for a few of the enzymes in our model [37]. We compared the fold change in protein abundance in HCC with respect to NL (no etiology information is present in the data) with those of the gene expression variations, and find them to be in good agreement, lending additional support to the hypothesis that the gene expression variations used in the model are biologically meaningful (Table S3).…”
Section: Generating Hcc-specific Modelsmentioning
confidence: 62%
“…In contrast, proteins participated in various metabolism pathways were down-regulated, indicating the suppression of metabolic functionality in liver during oncogenesis. Compared to a previous report of HCC tissue proteome using SWATH-MS 16 , our data are acquired in a shorter time frame but identified similar protein alternation. For instance, we also observed malignant tissue displayed increased abundance of glucose-6-phophate dehydrogenase (G6PD) and perilipin 2 (PLIN2), as well as downregulation of formimidoyltransferase cyclodeaminase (FTCD) and phosphoenolpyruvate carboxykinase 2 (PCK2, mitochondrial).…”
Section: Summary Of Regulated Proteins In Hcc Samplesmentioning
confidence: 63%
“…In a more recent study, Naboulsi W. et al identified and quantified 2,736 proteins from 19 pairs of HCC tumorous and adjacent non-tumorous tissue using the label-free shotgun proteomics over a 98-min LC gradient 15 . Gao et al 16 applied SWATH-MS to study 14 pairs of HCC and non-HCC tissues and quantified 4,216 proteins in at least one biological replicates and 1,903 proteins in at least three out of five biological replicates using a 120-min LC gradient. For each sample, about 200 mg tissue was used.…”
Section: Introductionmentioning
confidence: 99%
“…Sequential window acquisition of all theoretical spectra (SWATH/DIA-MS) is a newer method that combines the strengths of shotgun and targeted proteomics (Gillet et al, 2012). SWATH/DIA-MS is a label free and relatively cheap mass spectrometry method using data independent acquisition (DIA) combined with proteome wide spectral libraries created from data-dependent acquisition (DDA) methods against which the fragment ion maps of the DIA method are aligned (Gao et al, 2017;Gillet et al, 2012;Huang et al, 2015). Using the sequential isolation window acquisition has achieved high fragment ion specificity and the ability to identify and quantify thousands of proteins in one measurement (Gillet et al, 2012;Tang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%